Swipe to sustain: exploring consumer behaviors in organic food purchasing via instagram social commerce - Poureisa, Arman; Abdul Aziz, Yuhanis; Ng, Siew-Imm (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Promoting organic foods production and consumption contributes to accomplishing the United Nations’ sustainable development goals. Social commerce provides a promising opportunity to develop the organic food industry. However, there is limited knowledge regarding customer behaviors in relation to purchasing organic foods via social commerce platforms. Therefore, this study expanded upon the unified theory of acceptance and use of technology (UTAUT-2) to develop a comprehensive model that explains how customers’ social commerce trust and behavioral intentions to purchase organic foods using Instagram social commerce affect their purchasing behaviors. The research model was analyzed by employing partial least squares structural equation modeling (PLS-SEM) for the data collected from a quantitative survey of 410 customers who used Instagram to purchase organic foods in Iran. The results revealed that Instagram social commerce-facilitated purchasing conditions, hedonic motivations, social influence, ratings and reviews, and influencers’ endorsements positively influenced customers’ purchase intentions. Moreover, Instagram’s recommendations and referrals, influencers’ endorsements, as well as social influence boost customers’ trust in the social commerce platform. Eventually, it was determined that influencers’ endorsements, social commerce trust, and purchase intention determine a customer’s organic foods purchasing behaviors. This research provides valuable insights for organic food marketers to optimize their social commerce strategies. © 2024 by the authors.